Visual Analysis of Customer Behavior and Churn Triggers in the Telecommunications Industry: An Implementation of a BI Dashboard - Lestari, Tri Mukti; Nugroho, Fresy; Atnang, Muhammad (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2026)
The telecommunications industry faces the challenge of high customer churn rates, which can negatively affect company revenue and long-term business sustainability. This study aims to develop a Business Intelligence (BI)-based dashboard to visualize customer behavior and identify factors contributing to customer churn. A dataset consisting of 7,043 customer records was analyzed to discover churn patterns, develop predictive models, and perform customer segmentation. The proposed dashboard was designed as a user-friendly and interactive web-based platform to support data-driven decision-making. The results showed that 26.5% of customers experienced churn. The main factors influencing churn included monthly contracts, fiber optic service usage, the absence of online security and technical support services, and electronic payment methods. The findings also revealed that customers with higher monthly charges had a greater tendency to discontinue their subscriptions. User evaluation results indicated that the developed dashboard achieved a high level of usability and effectively presented customer information in a clear and understandable format. Therefore, the proposed BI dashboard can assist telecommunications companies in identifying at-risk customers and developing more proactive, targeted, and effective customer retention strategies.